Pengembangan Panduan Sinema Edukasi dengan Model Blended Learning untuk Menurunkan Prokrastinasi Akademik Siswa Sekolah Menengah Atas - Dinata, Wisnu Cahya; Rahman, Diniy Hidayatur; Indreswari, Henny (Buletin Konseling Inovatif, 2025)
This study aims to produce an educational cinema guide with a blended learning model to reduce academic procrastination of high school students who meet the acceptance criteria, including accuracy, usefulness, attractiveness, and convenience through material expert tests, media expert tests, and prospective users tests. This study adapts the development research design of Borg and Gall. The data generated are quantitative data and descriptive data. Quantitative data analysis used the inter-rater agreement model technique from Gregory. Descriptive data analysis was carried out by collecting criticism and input from experts and potential users, then used as material for product revision. The results of this product data analysis got a validation index from two material experts with a score of 1.00, two media experts got a score of 1.00, and two potential users got a score of 1.00, which means that all tests carried out have a very high validation index and fulfills the elements of acceptability, namely aspects of accuracy, usefulness, attractiveness, and convenience. This result means that the developed guide has been accepted and is suitable for school counselors to reduce the level of academic procrastination of high school students.